Myeloid-specific deletion of autotaxin inhibits rheumatoid arthritis and osteoclastogenesis - Heo, Gwangbeom; Jeong, Sihyun; Park, Soyeong; Kim, Su Jin; Lee, Yunna; Woo, Seong Ji; Kim, Kyunghwan; Park, Byung-Hyun; Rhee, Sang Hoon; Im, Eunok (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint swelling, pain, and bone remodeling. We previously reported that autotaxin (ATX) deficiency disrupts lipid rafts in macrophages. Lipid raft disruption results in the dysregulation of RANK signaling, which is crucial for osteoclastogenesis and the pathogenesis of RA. Therefore, we evaluated the effect of ATX deficiency on joint inflammation and osteoclast differentiation. A collagen-induced arthritis mouse model was used with myeloid lineage-restricted Atx-knockout (AtxΔME/ΔME) mice and DBA/1 mice treated with the ATX inhibitor PF-8380. Joint inflammation and bone erosion were visualized using hematoxylin and eosin staining and micro-computed tomography. Osteoclast differentiation was assessed by tartrate-resistant acid phosphatase staining. ATX deficiency suppressed joint inflammation, bone resorption, osteoclast differentiation, and pro-inflammatory protein expression in both AtxΔME/ΔME mice and PF-8380-treated mice compared to controls. Mean disease score of Atx+/+ mice at the end of experiment was 3.813, but that of AtxΔME/ΔME was 0.185 (p < 0.05). The differentiation of bone marrow-derived macrophages into osteoclasts was reduced in AtxΔME/ΔME cells compared to Atx+/+ cells. ATX deficiency suppressed RANKL-induced phosphorylation of ERK and Akt and the interaction between RANK and TRAF6. ATX deficiency disrupted lipid rafts and dysregulated RANK distribution in RAW264.7 cells. Actin ring formation was also inhibited in AtxΔME/ΔME osteoclasts. ATX deficiency suppressed RA and osteoclast differentiation by disrupting lipid rafts and altering the RANK signaling pathway. This suggests that ATX inhibition may be an effective strategy for developing new disease-modifying antirheumatic drugs.